Introgression from Gossypium hirsutum is a driver for population divergence and genetic diversity in Gossypium barbadense. (30th March 2022) - Wang, Pengpeng; Dong, Na; Wang, Maojun; Sun, Gaofei; Jia, Yinhua; Geng, Xiaoli; Liu, Min; Wang, Weipeng; Pan, Zhaoe; Yang, Qiuyue; Li, Hongge; Wei, Chunyan; et al.
Significance Statement: Interspecific introgression from Gossypium hirsutum has reorganized the genomic architecture of Gossypium barbadense . In this study, the genetic basis of population differentiation and the genetic diversity were deciphered and the introgression events and haplotype selection affecting associated fiber quality and environmental adaptation traits were illuminated in Gossypium barbadense . This study provides new insights into the breeding history of Gossypium barbadense and will guard the breeding programs of modern cultivated Gossypium barbadense . SUMMARY: During the domestication and improvement processes, interspecific introgression from Gossypium hirsutum has reorganized the genomic architecture of Gossypium barbadense ; however, the introgression details and the trait‐related genetic loci remain largely unknown. Here, we perform a genome‐wide population analysis and genetically recategorize 365  G. barbadense accessions into four subgroups which is different from previous categorizations. A total of 315 introgression events from G. hirsutum to G. barbadense, which primarily contributed to population divergence and agronomic trait variation in G. barbadense, are identified. We find that 70% introgression from G. hirsutum have greatly increased the genetic diversity and divergence of G. barbadense . Some loci are identified with divergent haplotype selection for adaptation to the environment at high latitudes. Through genome‐wide association study and genome linkage disequilibrium interval haplotyping analyses, two fiber micronaire‐related haplotype blocks are detected, one of which ( FM2 ) is introgressed from G. hirsutum . Seven distinguished traits related to growth period, plant architecture, and stronger vegetative growth habit are found to have pleiotropic effects controlled by a single gene in G. barbadense . Thus, this study provides new insights into the breeding history of G. barbadense and highlights introgression is a driver for improving cultivars in G. barbadense .